PERILAKU FANATISME PENGGEMAR BUDAYA MUSIK POP KOREA GRUP EXO DI KOTA PONTIANAK - Lestari, Wiji (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
Writing this thesis is intended to provide an understanding of the fanatic behavior of fans of Korean pop music culture group EXO in Pontianak City. Fanaticism is a behavior that is beyond the individual's own control so that it can make someone become addicted or fanatical about something or an object. The research method used is descriptive research with a qualitative approach. The subjects of this research were fans of the EXO group who had experienced fanaticism. The location of this research is in Pontianak City. The selection of informants was carried out using a purposive sampling technique, while the data collection technique was through the stages of observation, interviews and documentation. In this research, the author carried out an observation and interview process with 7 sources who were selected based on predetermined criteria using purposive sampling. The results of this research show that there are two kinds of factors that influence a person's behavior to become a fanatic, namely internal behavior and also external/social behavior. Internal behavior is an action or all behavior that originates from within the individual himself, where no one can see and feel it except himself. Meanwhile, external or social behavior is any action that arises from outside a person and is usually caused by factors within the individual's surroundings. Apart from that, there are also 3 basic assumptions that make a person have fanaticism, namely behavior is lawful, behavior and behavior that cannot be controlled